Gestión de cartera en empresas privadas prestadoras de servicios hospitalarios - Cárdenas Marín, Darwin Emilio (2021)
According to the established objectives, this research will allow to analyze the portfolio management applied by private companies that provide hospital services; to demostrate the leve lof compliance and suggest corrective and preventive measures if the case warrants it; which will allow compensation for the services provided to be carried out as determined by current legal regulations. The lack of timely compensation by Financiers / Payers, has caused thet several private companies that provide hospital services that signed agreements to provide their services to fifferent patients, have had to suspend their activities as avalanche providers and even caused the closure of private companies that provide hospital services, as they did not recover the expenses incurred in providing the services, which affected the liquidity of the companies………